2015
DOI: 10.4103/0972-6748.181729
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction and its determinants among medical students

Abstract: Background:Exponential use of internet has resulted in internet addiction in recent times. Students are particularly at risk because of their unique personal, social, and academic needs.Objectives:The study was designed to evaluate the prevalence of internet addiction and its determinants among medical students.Materials and Methods:A cross-sectional study was conducted in 282 medical students with the help of semi-structured questionnaire consisting of questions related to demographic information, information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
52
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 21 publications
10
52
2
Order By: Relevance
“…The present study findings are similar to prevalence rates of moderate IA reported by other Indian studies which ranged from 7.45% in medical students,[ 37 ] to 7.4%[ 31 ] and 15.2% in university undergraduates. [ 38 ] A study from Iran indicated 8% of university students were engaged in moderate levels of IA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study findings are similar to prevalence rates of moderate IA reported by other Indian studies which ranged from 7.45% in medical students,[ 37 ] to 7.4%[ 31 ] and 15.2% in university undergraduates. [ 38 ] A study from Iran indicated 8% of university students were engaged in moderate levels of IA.…”
Section: Discussionsupporting
confidence: 91%
“…Engineering students were staying away from their families, in rented accommodations were at a higher risk of developing IA. This study finding is in alignment with studies done in India[ 37 ] and Iran[ 51 ] which too suggested IA is higher among students who stay independently. The experience of loneliness, boredom, availability of privacy, ease of internet access, and minimal presence of parental supervision are factors which likely increase excessive use of internet.…”
Section: Discussionsupporting
confidence: 91%
“…The present study findings are similar to prevalence rates of moderate IA reported by other Indian studies which ranged from 7.45% in medical students[ 39 ] to 7.4%[ 33 ] and 15.2% in university undergraduates. [ 40 ] A study from Iran indicated 8% of university students were engaged in moderate levels of IA.…”
Section: Discussionsupporting
confidence: 92%
“…University students staying away from their families, in rented accommodations, were at a higher risk of developing IA. This study finding is in alignment with studies done in India[ 39 ] and Iran[ 50 ] which too suggested IA is higher among students who stay independently. The experience of boredom, loneliness, and availability of privacy, ease of the Internet access, and minimal presence of parental supervision are factors which likely escalate the excessive use of the Internet.…”
Section: Discussionsupporting
confidence: 91%
“…[ 27 ] However, certain other studies have reported that more number of years of internet usage was associated with higher risk for IA. [ 11 28 ]…”
Section: Discussionmentioning
confidence: 99%